Microbiological spectrum of nosocomial infection in patients with infectious spondylitis after sepsis - A. A. Vishnevskiy; N. S. Solovieva (Журнал инфектологии, 2019)
In 2015—2017, a cohort study of 72 cases of infectious spondylitis (is) with severe sepsis was conducted, which amounted, to 5,8% of all operated, patients. The study showed, that Gram. (+) bacteria -52 (55,9%) prevailed, in crops from all media. Gram. (-) bacteria were detected, in 1\3 cases 37(39.8%), and Candida infection in 4 (4,3%).The main traced, sources of NI in patients with is where bedsores (13\18,1%), infection with surgical intervention, fistula (14\19,4), uroinfection (22\30,6%), subclavian catheters (7\55.5%). Gram. (+) bacteria was 26,8% (15 cases) and was mainly found, in wounds and. catheters. Gram. (-) bacteria more prevalent in ulcers in the urine culture (56,4 per cent). In 10 cases (17,8%) the crops were sterile. An increase in the role of S. epidermitis and. K. pneumoniae in the etiology of sepsis was found, in bacteriological typing of media. High resistance of nosocomial strains of Staphylococcus spp is noted. Gram. (-) bacteria to fluoroquin.alon.es and. cephalosporins 3—4 generations, which excludes the possibility of their empirical use in the treatment of severe sepsis in patients with is.